Coping with workplace minority stress: Associations between dyadic coping and anxiety among women in same-sex relationships. Issue 1 (2nd January 2017) - Randall, Ashley K.; Totenhagen, Casey J.; Walsh, Kelsey J.; Adams, Caroline; Tao, Chun
ABSTRACT: Sexual minorities are exposed to stressors in the workplace (workplace minority stress), which can be detrimental for well-being (e.g., levels of anxiety). The present study examined whether a particular set of relationship processes, dyadic coping, served to moderate the association between workplace minority stress and symptoms of anxiety. Using a dyadic sample of 64 female same-sex couples, we found that partner problem-focused supportive dyadic coping (DC) and emotion-focused supportive DC (marginally) buffered, whereas partner delegated DC and negative DC did not moderate, the association between workplace minority stress and symptoms of anxiety. Implications for relationship researchers and mental health practitioners are discussed.